2008
DOI: 10.1111/j.1600-0897.2008.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Decidual Natural Killer Cell Tuning by Autologous Dendritic Cells

Abstract: These results suggest that decidual CD1a(+) cells regulate and shape NK cell function more profoundly than CD83(+) cells in decidua.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 28 publications
(36 reference statements)
1
40
1
Order By: Relevance
“…It has been shown that self-reactive T cell clones can be restricted by either of CD1a and CD1d molecules [40]. In addition, tight regulation of NK cell function by CD1a+ DCs in the human deciduas may affect successful implantation of the embryos [43]. Interestingly, there are existing evidence on the cross regulation of CD1a expression on iDCs by CD1d-dependent iNKT cell responses [44].…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that self-reactive T cell clones can be restricted by either of CD1a and CD1d molecules [40]. In addition, tight regulation of NK cell function by CD1a+ DCs in the human deciduas may affect successful implantation of the embryos [43]. Interestingly, there are existing evidence on the cross regulation of CD1a expression on iDCs by CD1d-dependent iNKT cell responses [44].…”
Section: Discussionmentioning
confidence: 97%
“…iDCs may play a role in CD56 1 NK cell recruitment, proliferation and inhibitory receptor expression (Figure 2a) as shown by CD56 1 NK cell and decidual iDC coculture, demonstrating that only one-third of NK cells proliferated in contact with iDC cells. 11 This suggests a selective expansion of NK cells by iDCs that is beneficial for pregnancy outcome. Additionally, NK cells proliferate and increase inhibitory receptor expression in response to iDC-derived IL-15.…”
Section: Nk/dc Liaison At the Fetomaternal Interfacementioning
confidence: 99%
“…21 DC-SIGN 1 DCs are also able to secrete IL-15 during decidualization and embryo implantation. 11,22 This secretion then recruits decidual NK cells to the endometrium 23 and upregulates CD56 expression. 24 Previous works state that decidua tissues from spontaneous abortions contain fewer DC-SIGN 1 iDCs compared with normal decidua, and iDC maturation and migration out of the decidual tissue to initiate an immune response might explain this phenomenon.…”
Section: Human Dcsmentioning
confidence: 99%
See 2 more Smart Citations